Photoaffinity labeling for structural probing within protein - Hatanaka, Yasumaru; Hashimoto, Makoto (Springer, 2017)
This book covers the most up-to-date photoaffinity labeling method to tackle the key loop module involved in the binding process of a bioactive small molecule to its host protein. The book introduces rational points for preparing powerful photoaffinity probes, keys for the efficient analysis of labeled products, and recent successful applications for protein probing. Regarding drug design, the unique topics of the book are the special consideration of the crosslinking potential of recent probes and their application of important receptor proteins . This book presents emerging technologies of photoaffinity labeling to readers who are working in the fields of proteomics, molecular recognition, and drug discovery and development.
Keywords: Photoaffinity labeling.; Proteins -- Structure.; elektronické knihy; electronic books